Desarrollo de un sistema basado en conocimiento usando RNA para el apoyo al diagnóstico de trastornos depresivos en la oficina general de Bienestar Universitario de la Universidad Nacional de Trujillo - Hoyos Iparraguirre, Kevin (2017)
The National University of Trujillo has the area of Psychology in the General_x000D_ Office of University Welfare, which is responsible for the care, evaluation, diagnosis_x000D_ and treatment of students who go to that area. There is only one Psychologist in_x000D_ this area, and when there is a need to diagnose if a patient has any type of Depressive_x000D_ Disorder, he does not have a mechanism to help him evaluate and diagnose his_x000D_ patients in a fast and efficient way, since The psychologist uses a practically manual_x000D_ method to evaluate and diagnose his patients._x000D_ This is why the need arises to implement a tool to support the Psychologist_x000D_ in the diagnosis of Depressive Disorders, in order to streamline and optimize the_x000D_ evaluation process and the diagnosis of patients._x000D_ The mentioned tool consists of the implementation of a Knowledge Based System_x000D_ (SBC) using Artificial Neural Networks (RNA), and for its modeling and development_x000D_ was used the Methodology of Knowledge Engineering proposed by John_x000D_ Durkin._x000D_ The final results of the investigation were satisfactory, since the system was_x000D_ able to diagnose with a high percentage of certainty. In addition, it was possible to_x000D_ provide a technological tool to support the Psychology specialist, improving their_x000D_ performance in the diagnostic process of Depressive Disorders